THE EXISTENTIALIST FEMINISM IN P.J HOGAN’S CONFESSION OF A SHOPPAHOLIC FILM - Dita Herma Yulistya; Indah Lestari (Universitas Negeri Islam Sumatera Utara, 2024)
The social phenomena of women and gender arises because of the discrimination between men and women. Whereby, the women are not respected in taking opportunities and decisions within life and it control of women’s freedom. Thereby, women is struggling in their existence to equal like men. The problem undertaken in this research relate to feminism, specifically on types existentialist feminism in perspective by Simone De Beauvoir’s The Second Sex book. The focus of this research is to find out the main character existence that relates to the freedom of Rebecca’s choice in Confession of a Shopaholic film. This research used a qualitative descriptive method and data taken from Confession of a Shopaholic film. The result revealed three types of existentialist feminism from the P.J Hogans’s Confession of a Shopaholic film and each of the data found in this research are 10 data of prostitutes, 9 data of narcissism, and 12 data of mystic. Also, Rebecca is a woman who achieves freedom in determining her own life choices, whose her freedom is shopping, and what she doing for her existence as a woman is seen by other women that Rebecca is able to shop for the same luxury goods.